Pengaruh Literasi Keuangan dan Inklusi Keuangan Terhadap Keberlanjutan UMKM Jakpreneur di Jakarta Barat dengan Penggunaan Fintech sebagai Variabel Intervening - Giffary Aulia Rachman; RD. Tuty Sariwulan; Dicky Iranto (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study aims to analyze the influence og financial literacy and financial inclusion on the sustainability of Jakpreneur MSMEs in West Jakarta with fintech utilization as an intervening variable. The research employs a quantitative approach using a survei method involving 397 Jakpreneur MSME actors in West Jakarta. Data were analyzed using Partial Least Squares – Structural Equation Modelling (PLS-SEM) through SmartPLS 4.0 software. The result indicate that Financial Literacy has a positive and significant effect on MSME Sustainability. Financial Inclusion has a positive and significant effect on MSME Sustainability. Fintech has a positive and significant effect on MSME Sustainability. Financial Literacy has a positive and significant effect on Fintech. Financial Inclusion has a positive and significant effect on Fintech. Financial Literacy has a positive and significant indirect effect on MSME Sustainability through Fintech. Financial Inclusion has a positive and significant indirect effect on MSME Sustainability through Fintech. These findings highlight that improving financial management capability, access to formal financial services, and the adoption of financial technology are key factors in strengthening the resilience and growth of MSMEs in the digital era.